2008
DOI: 10.1002/cjce.20017
|View full text |Cite
|
Sign up to set email alerts
|

Hydrosulphide oxidation pathways in oxic alkaline media containing iron/cerium oxide‐hydroxide

Abstract: The oxidation kinetics of hydrosulphide by iron/cerium oxide‐hydroxide (FeCeOx) and dissolved oxygen (DO2) was studied at 0.1 MPa and 298 K in a batch slurry reactor. The oxidation of hydrosulphide by the FeCeOx/DO2 system proceeded via a combined heterogeneous–homogeneous pathway to yield zerovalent sulphur and thiosulphate. The role of dissolved oxygen was twofold: (i) it reoxidized the iron from Fe(II) to active Fe(III), (ii) it prompted the homogeneous oxidation of hydrosulphide to polysulphides and of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In oxic conditions, Petre and Larachi (2007d) reported that the oxidation of HSby the Fe/CeOx0.9/DO 2 system proceeded with conversions up to 100% to yield zerovalent sulfur and thiosulfate. The role of DO 2 was found to be twofold: i) it reoxidized the ferrous iron (via Eq.6), yielded from HSoxidation, to replenish the surface with Fe(III) sites for restoring full oxidative capability of the material towards HS -, ii) it prompted the homogeneous oxidation of HSto polysulfides and of polysulfides to thiosulfate (see Section 4.4).…”
Section: Removal Of Hsby Fe/ce Oxides-hydroxides In Anoxic and Oxic Amentioning
confidence: 99%
See 1 more Smart Citation
“…In oxic conditions, Petre and Larachi (2007d) reported that the oxidation of HSby the Fe/CeOx0.9/DO 2 system proceeded with conversions up to 100% to yield zerovalent sulfur and thiosulfate. The role of DO 2 was found to be twofold: i) it reoxidized the ferrous iron (via Eq.6), yielded from HSoxidation, to replenish the surface with Fe(III) sites for restoring full oxidative capability of the material towards HS -, ii) it prompted the homogeneous oxidation of HSto polysulfides and of polysulfides to thiosulfate (see Section 4.4).…”
Section: Removal Of Hsby Fe/ce Oxides-hydroxides In Anoxic and Oxic Amentioning
confidence: 99%
“…Based on their experimental observations, Petre and Larachi (2007d) proposed a simple kinetic model depicting the early 20 min of the global reaction between HSand Fe/CeOx0.9 in presence of oxygen. The model is adapted on the HSanoxic heterogeneous oxidation kinetics (Eq.…”
Section: Removal Of Hsby Fe/ce Oxides-hydroxides In Anoxic and Oxic Amentioning
confidence: 99%